Mahishasuramardini Temple (Temple 9) - Temples of India Project Team (Jio Institute, 2024)
Temple 9 is dedicated to Mahishasuramardini. Presently, the temple is in a dilapidated condition, with many parts of the temple scattered around due to collapses. The temple faces west and comprises a garbhagriha (sanctum sanctorum), antarala (vestibule), and a mukhamandapa (front porch). Unfortunately, the mandapa (pillared hall) and the antarala have collapsed.